Dose-Response Curve of Chromosome Aberrations in Human Lymphocytes Induced by Gamma-Rays - Y. Lusiyanti; Z. Alatas; M. Lubis; V.A. Suvifan; D. Ramadhani; S. Purnami (Atom Indonesia, 2013)
Chromosome aberration is a biomarker to predict the level of cell damage caused by exposure to ionizing radiation on human body. Dicentric chromosome is a specific chromosome aberration caused by ionizing radiation and is used as a gold standard biodosimetry of individuals over exposed to ionizing radiation.In radiation accident the dicentric assays has been applied as biological dosimetry to estimate  radiation absorbed dose and also to confirm the radiation dose received to radiation workers.The purpose of this study was to generate a dose response curve of chromosome aberration (dicentric) in human lymphocyte inducedbygamma radiation. Peripheral blood samplesfrom three non smoking healthy volunteers aged between 25-48 years old with informed consent were irradiated with dose between 0.1-4.0Gy and a control using gamma teletherapy source. The culture procedure was conducted following the IAEA standard procedures with slight modifications. Analysis of dose-response curves used was LQ model Y = a + αD + βD2. The result showed that α and β values of the curve obtained were 0.018± 0.006 and 0.013 ± 0.002,respectively. Dose response calibration curve for dicentric chromosome aberrations in human lymphocytes induced by gamma-radiation fitted to linear quadratic model. In order to apply the dose response curve of chromosome aberration disentric for biodosimetry, this standar curve still need to be validatedReceived: 8 November 2013; Revised: 27 December 2013; Accepted: 31 December 2013